Geometric morphometric divergence of five populations of Pampus argenteus (Euphrasen, 1788) from Malaysian waters - SUZYELAWATI MOHD SHUKRI; KHALED BINASHIKHBUBKR; AHMAD DWI SETYAWAN; DARLINA MD NAIM (Nusantara Bioscience, 2024)
Abstract. Shukri SM, Binashikhbubkr K, Setyawan AD, Md. Naim D. 2024. Geometric morphometric divergence of five populations of Pampus argenteus (Euphrasen, 1788) from Malaysian waters. Nusantara Bioscience 16: 1-12. Phenotypic variation in fish may indicate different environmental conditions that affect species' growth and maturation rates and result from genetic factors that allow fish to adapt to different environments. Understanding population structure and dynamics is extremely important for establishing sustainable fisheries. Silver pomfret, Pampus argenteus (Euphrasen, 1788), is an economically important fish species with extensive geographical distribution from the East China Sea to Southeast Asia, Indian Ocean, Arabian Gulf, and the North Sea. It may represent morphologically distinct populations across their range. The main aim of this study is to use geometric morphometric analysis based on physical characteristics to look into the phenotypic diversity of the species across five different populations in Malaysia. Digital images of 260 mature specimens were captured for further analysis. Principle Component Analysis (PCA) and Multivariate analysis (MANOVA) were used in the intra-population analysis based on the transformed distance. At the same time, the Canonical Variance Analysis (CVA) and the Procrustes ANOVA were utilized to determine the inter-population analysis of P. argenteus. The Unweighted Pair Group with Arithmetic Mean (UPGMA) method used to support the analysis has shown that the population is clearly grouped according to homologous body shape. The results show that South, West, and North Coast specimens were grouped while the East Coast and Borneo Island shared in another group. The variations in the body shape of P. argenteus occurred in body depth, caudal region, and head orientation. The findings separated the populations into two main groups representing the marine region to which they belong. This present study is the first report on phenotypic variations of P. argenteus from Malaysian waters utilizing the geometric morphometric method.